Cobalt mediated perovskite as efficient Fenton-like catalysts for the tetracycline removal over a neutral condition: The importance of superoxide radical. (February 2023) - Li, Jinxin; Zhong, Dan; Huang, Jianyang; Ma, Wencheng; Li, Kefei; Li, Menglin; Wu, Rui; Pu, Congqiao; Wang, Qi; Zhou, Yuzhe; Zhang, Shaobo
Abstract: Cobalt mediated perovskite oxides (Ca–Fe–Co- x ) were prepared for heterogeneous Fenton-like, which exhibited excellent tetracycline (TC) degradation efficiency and wider pH suitability (3–11). Experimental results showed that Ca–Fe–Co-1.0 sample displayed the highest degradation rate could reach 80.5% under neutral conditions, and maintain at around 80% after four cycles. The analysis of degradation mechanism showed that the redox of Fe 2+ /Fe 3+ and Co 2+ /Co 3+ significant enhanced the activation of H2 O2 to superoxide radical (∙O2 − ). Meanwhile, the hydroxyl radical (∙OH) was also detected by ESR analysis. In addition, the possible degradation pathway and mechanism of TC were deduced via UPLC-QTOF/MS analysis and density functional theory (DFT) calculations. The toxicity of TC and its intermediates were also evaluated by the ECOSAR software. The Ca–Fe–Co-1.0/nanocellulose aerogel (NCA) displayed highly removal efficiency of TC wastewater in the long-term operation conduction. This study provided a feasible method to design and synthesis heterogeneous Fenton-like catalysts for antibiotic degradation. Graphical abstract: Image 1 Highlights: Cobalt mediated perovskite would promote H2 O2 decompose to superoxide radical. DFT calculations prove that cobalt enhance the electron transfer in perovskite. Degradation intermediates were identified, and possible pathways were proposed. Ca–Fe–Co/NCA displayed excellent efficiency in the continuous experiments.